PS01.046: ENDOSCOPIC THERAPY FOR ESOPHAGEAL VARICES IN THE ELDERLY CAN BE PERFORMED IN SAFETY. (14th September 2018) - Sasaki, Ryo; Iwamoto, Takuya; Nishimura, Tatsuro; Sakaida, Isao
Abstract: Background: In this study, we evaluated the risk of complications and the effects of the treatment of esophageal varices in elderly patients with cirrhosis, by comparing the data of elderly and non-elderly patients. Methods: We included 284 patients who received endoscopic therapy for esophageal and gastric varices at our hospital between February 2004 and December 2016 in the study.The subjects were divided into two groups.An elderly group comprising patients who were 65 years of or order.A Non-elderly group comprising patients who were under 65 yearsWe compared various parameters such as blood data before and after the endoscopic therapy, as well as the complications associated with the treatment, and then performed statistical analyses on the results. Results: Of the 284 subjects, 168 patients were elderly group 65 years or older and 116 patients were non-elderly groupaged less than 65 years. Complications were observed in 30 of 168 subjects (17.8%) in the elderly groupwho were aged 65 years or greater and in 25 of 116 subjects (21.6%) under 65 yearsin the non-elderly group, which did not indicate a significant difference between the two groups. The Child-Pugh score was 6.6 ± 0.1 in the elderly group and 7.1 ± 0.2 in the non-elderly group, indicating that the score was significantly lower in the elderly group ( P  < 0.05). Our investigation of the patients' medical history pertaining to liver complications indicated that 32.3% of the subjects in the non-elderly group were alcoholics, as compared to 14.8% in the elderly group, indicating a significantly higher percentage of alcoholics in the non-elderly group ( P  < 0.01). Our investigation of the efficacy of the treatment of varices indicated that the recurrence rate within 1 year was 29.2% in the elderly group and 28.0% in the non-elderly group, indicating that there was no significant difference between the two groups. Conclusion: Our study comparing the endoscopic treatment of esophageal varices in the elderly and the non-elderly revealed that there were no significant differences in the increase in the risk of complications or the efficacy of treatment. Therefore, we believe aggressive treatment shouldmay be considered even for elderly patients to avoid the risk of variceal rupture and bleeding. Disclosure: All authors have declared no conflicts of interest.